The Road to Service Export Diversification: Gambling and Convention in Macao - Lei, Weng Chi (Economics and Finance Readings: Selected Papers from Asia-Pacific Conference on Economics & Finance, 2019, 2020)
This book is a compilation of the best papers presented at the APEF 2019 conference which was held on 25th and 26th July 2019 at the Grand Copthorne Waterfront in Singapore. With a great number of submissions, it presents the latest research findings in economics and finance and discusses relevant issues in today's world. The book is a useful resource for readers who want access to economics, finance and business research focusing on the Asia-Pacific region.

Oligopolistic Strategies in the Gaming and Hospitality Industries of Macau - Leong, Chi Leng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Nowcasting Gross Domestic Product and Gross Gaming Revenue of Macau: a Theoretical and Conceptual Framework - Chau, Manuel; Lei, Weng Chi (2021)
This paper aimed to build up the theorical and conceptual understanding of future forecasting study of Macau’s GDP and Gross Gaming Revenue (GGR) by co-movement of economic indicators. Macau GDP and GGR showed co-movements with a number of time series economic indicators, including China’s exports and imports, China’s manufacturing PMI, non-manufacturing PMI, China's electricity production growth, share price of some Macau’s gaming operators, etc. These time series data can be found in statistics departments of China, Macau and Hong Kong, stock exchanges, and international organizations such as the International Monetary Fund (IMF), the World Bank, the World Trade Organization (WTO). Burns and Mitchell’s study in 1946 identified co-movements between economic indicators and being further carried out and developed leading, coincident and lagging indicators, which is essential for future econometric models and nowcasting techniques developments to study these co-movements. In particular, with the proper application of nowcasting techniques, future studies can exploit the data of leading and coincident economic indicators to forecast Macau’s GDP and GGR within an acceptable level of error. Since Macau is a “monotown,” where the gaming revenue makes a significant contribution to the economy. The forecasting of gaming revenue is crucial as it aids the gambling and tourism industries in preparing supply and provides information to policymakers to plan for the near future. This research also contributes to understand Macau’s economy by investigating its internal and external economic variables.

Mandatory Provident Fund Scheme: Prespectives of Macau Employees - Cheong, Kit I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

IMPACTS OF CHINA’S ENTRY ON THE PRODUCT LINE RIVALRY IN THE GLOBAL CIVIL AIRCRAFT INDUSTRY - Chen, Yawen (University of Saint Joseph, 2024)
As international tourism continues to flourish and airlines are eager to expand their fleets, the demand for civil aircraft has continues to grow in the global market. The market has been a duopolistic one, shared by Boeing and Airbus. However, the recent entry of the Chinese company, Comac, had the potential to turn it into a triopoly within certain segment of the product line. This observation motivates the research objective to analyze the impact of Comac's entry on the production strategies of the incumbents. Specifically, this dissertation studies the impact on each firm’s allocation of production capacity toward different civil aircraft in the product line in response to how Comac’s entry, which can also impact the effects of capacity increase and market expansion on the product line rivalry. This dissertation is based on a multi-product, oligopolistic model of Boeing and Airbus. To provide insights on the strategy and behavior of each firm in the evolving competitive environment, this dissertation solves and extends the mathematical model to incorporate Comac as the entrant and compares model results with data of orders and deliveries of the three companies in the past 15 years. This model finds that when Comac's C919, a relatively small plane, enters the global civil aircraft market, Boeing and Airbus will increase the production of their small planes and decrease the production of the relatively large planes under the production capacity constraints. If the production capacity increases, both Boeing and Airbus will produce more planes, but will allocate more additional capacity to large planes than to small planes compared to the duopolistic competitive environment. When the market demand increases, despite the entry of the C919, Boeing and Airbus iv will continue to increase the production of both large and small planes, but the response is greater to an increase of demand for large planes than that for small planes. The orders and deliveries data provide some but insufficient support for the model predictions. As the market participation of Comac continues to grow, future researchers can re-assess the models’ propositions with more available data
Keywords: Capacity allocation; Civil aircraft; Comac; Duopoly; Oligopoly; Product line rivalry; Thesis and Dissertations Master of Business Administration (MBA); Triopoly; University of Saint Joseph

Impacts of Central Bank Digital Currency on Regional Economic Integration: Evidence from the Greater Bay Area of China - Lei, Weng Chi; Wang, Xinru (The Chinese Economy, 2024)
An increasing number of countries have launched their central bank digital currencies (CBDC) in recent years, but the economic impacts of CBDC adoption are underexplored. To empirically assess how CBDC adoption influences regional economic integration, this paper investigates the Greater Bay Area, where China carried out one of its first digital renminbi pilot programs. The Greater Bay Area provides a good example because the growing acceptance of digital renminbi in the area can potentially mitigate transaction costs and risks due to the exchange rate volatility of the Chinese renminbi, Hong Kong dollar, and Macao pataca. CBDC adoption can lead to greater real and financial integrations by facilitating cross-border trade in goods and services. This paper evaluates deviations from uncovered interest rate parity, purchasing power parity, and real interest rate parity across Guangdong, Hong Kong, and Macao based on monthly interest rate and price data from January 2016 to December 2022. The time series have mean values near zero, which validate the parity conditions and indicate high degrees of financial, real, and economic integrations. The Markov regime-switching regression model identifies three regimes: (1) pre-Covid, (2) post-Covid, and (3) post-CBDC. The Covid-19 outbreak brought lower integration and stability, but the launch of the CBDC restored some of the pre-Covid integration and stability. Regimes 1 and 2 are persistent, and transitions from Regime 3 back to Regime 1 are probable. Hence, this study finds evidence that CBDC adoption improves regional economic integration in the short and long run.
Publisher: Routledge _eprint: https://doi.org/10.1080/10971475.2024.2333124
Keywords: Central bank digital currency; Greater Bay Area; digital renminbi; economic integration; financial integration

IMPACTS OF CARBON TRADING SYSTEM ON GREEN FINANCE: Ziyan Yin - Yin, Ziyan (University of Saint Joseph, 2024)
Against the backdrop of escalating global climate change and China being the world’s largest carbon emitter, this study explores the impact of the carbon trading system on green finance in Chinese power sector. This study uses a quantitative research method, namely a difference-in-differences (DID) model, to investigate power companies that participated or had the potential to participate in carbon trading in 2019 and 2022. The key finding is that companies that participated in carbon trading had significantly higher green finance than those that did not participate, indicating that the carbon trading system has a positive impact on promoting green finance. However, the impact does not significantly intensify after the national carbon trading scheme was implemented in mid-2021. The green finance of listed companies and state-owned enterprises were less affected by carbon trading, possibly because these companies rely on alternative financing options and government financial support. Due to the findings, this study recommends that policy makers should strengthen the promotion of the carbon trading scheme and provide more support for non-listed companies and non-state-owned enterprises. At the same time, the companies should actively participate in the carbon market to take advantage of the industrial policies to enhance green finance, and ultimately promote environmental protection and their own sustainable development
Keywords: Carbon trading scheme; Carbon trading system; China; DiD; Difference-in-difference; Green finance; Power companies; Power plants; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Impact of Education on Green Fintech Adoption in a Smart City: Evidence from the Newly Developed Sub-city Center of Beijing. - Lei, Weng Chi; An, Boyang (PROCEEDINGS OF THE 18th INTERNATIONAL CONFERENCE OF THE AGBRP, 2024)
Integrating financial technologies with green initiatives is critical to the sustainable development agenda. This is particularly true for newly developed smart cities like Tongzhou, the sub-city center of Beijing. To assess the adoption of green fintech in Tongzhou, this paper extends the EnergyAugmented Technology Acceptance Model (EA-TAM) to incorporate two green factors – environmental awareness and green knowledge. This paper applies structural equation modeling techniques to analyze data from 403 respondents who live, work, or study in Tongzhou and finds allhypothesized constructs significant. Since green knowledge is significant to the adoption of green fintech, this paper further divides the sample into a high-education group (162 respondents with university-or-above degrees) and a low-education group (251 respondents with post-secondary-orlower degrees) to evaluate the impact of education. All the hypothesized factors are significant to the high-education group,but environmental awareness and perceived usefulness are insignificant to the low- education group. Hence, the results provide evidence that people in the newly developed smart city adopt green fintech due to their environmental sensitivity. The adoption of green fintech is more environmentally sensitive for people with high education levels.

Impact of Education on Green Fintech Adoption in a Smart City: Evidence from the Newly Developed Sub-city Center of Beijing. - Lei, Weng Chi; An, Boyang (2024)
Integrating financial technologies with green initiatives is critical to the sustainable development agenda. This is particularly true for newly developed smart cities like Tongzhou, the sub-city center of Beijing. To assess the adoption of green fintech in Tongzhou, this paper extends the EnergyAugmented Technology Acceptance Model (EA-TAM) to incorporate two green factors – environmental awareness and green knowledge. This paper applies structural equation modeling techniques to analyze data from 403 respondents who live, work, or study in Tongzhou and finds allhypothesized constructs significant. Since green knowledge is significant to the adoption of green fintech, this paper further divides the sample into a high-education group (162 respondents with university-or-above degrees) and a low-education group (251 respondents with post-secondary-orlower degrees) to evaluate the impact of education. All the hypothesized factors are significant to the high-education group,but environmental awareness and perceived usefulness are insignificant to the low- education group. Hence, the results provide evidence that people in the newly developed smart city adopt green fintech due to their environmental sensitivity. The adoption of green fintech is more environmentally sensitive for people with high education levels.

Fintech Services in Guangdong-Macao in Depth Cooperation Zone in Hengqin: An investigation of Macao Users' Adoption - Kuan, Chi Hou (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

EVALUATING SATISFACTION OF LOCAL ROAD USERS OF MACAU - Fong, Chi Cheng; Pinheiro, Francisco Vizeu; Lei, Weng Chi (University of Saint Joseph, 2023)
"Macau's rapid economic development in recent decades and relatively low usage of public transportation have put considerable pressure on the city's carrying capacity. Improving the transportation system has been a major policy goal of Macau's urban planners. To deepen the understanding of the perspectives of local road users, this dissertation's main research question is: what factors determine the satisfaction of local road users of Macau? After collecting responses using an online questionnaire, quantitative research methods were adopted to analyze travel patterns, satisfaction toward different road usage dimensions, and sociodemographic characteristics of local residents. 145 responses were collected and quota samples were generated to match the distribution of each sociodemographic feature of the population. Most respondents used private vehicles to travel during peak hours on weekdays for work or for school and to travel during the entire afternoon and evening on weekends for shopping necessities and for leisure. The most traveled districts were Baixa de Taipa, Costa & Ouvidor Arriaga, and Baixa de Macau. It was found that the mean overall satisfaction score inclined to the dissatisfaction side (below 3). Only clarity of traffic lights and number of road signs (measuring infrastructure) and temperature and price of fares (measuring public transportation) had mean satisfaction scores that were significantly higher than 3, indicating higher satisfactions. Meaningful hypotheses regarding the differences of different road user groups were set out, then Kruskal-Wallis ANOVA tests and Mann-Whitney U tests were run. The significant findings were such that the elderly aged 65 or above were less satisfied and the unemployed were more satisfied with road usage. The better educated were more satisfied with the environment, and the unemployed were more satisfied with the public transportation. Drivers were less satisfied with transportation costs, and peakhour road users were less satisfied with the infrastructure. The Spearman correlation analyses found that infrastructure had moderately positive correlation with facilities and with travel safety. Based on the findings and their policy implications, policy suggestions could be made. The policies suggested in this study should have favorable short-term and long-term effects on more than one road usage aspects."
Keywords: Public transport; Survey questionnaire; Thesis and Dissertations Master of Government Studies (MGS); Traffic congestion; Transportation; Transportation services; University of Saint Joseph

Economic Integration in the GBA: a Price-Based Assessment of Real and Financial Integration in the Greater Bay Area - Lei, Weng Chi; Wang, Xinru (2022 13th International Conference on E-business, Management and Economics, 2022)
The Guangdong-Hong Kong-Macau Greater Bay Area (GBA) was first conceptualized in 2016, which aimed to facilitate trade and finance liberalization among the three regions. The trade and financial environment of the GBA is unique. Due to the “one country, two systems” principle, Mainland China, Hong Kong and Macau are considered to be trading partners bounded by WTO rule, but bilateral free trade agreements have been signed between Mainland China and Hong Kong, and between Mainland China and Macau, but not between Hong Kong and Macau. Furthermore, each of the three regions circulates a local currency subject to its own exchange rate policy, with Hong Kong Dollar and Macau Pataca currently pegged to the US Dollar. These affect the mobility of trade and capital flows in the area. Hence, this paper applies the widely-used price-based approach due to Cheung et al. [5] to analyze the degrees of real and financial integration in the GBA based on interest rates, exchange rates, and price indexes data from January, 2016 to November, 2021. The real interest differential (RID), uncovered interest differential (UID) and the deviation from purchasing power parity (PPD) between each regional pair have means that are statistically and economically close to zero, implying high real and financial integration in the GBA. The unit root tests for stationarity also confirm that the time series are mean-reverting, so the economic integration in the GBA in the long run is foreseeable.
0 citations (Crossref) [2023-03-15]
Keywords: Economic development policy; Economic integration; Financial Integration; Greater Bay Area

Digital Renminbi: Impacts on Economic Integration of the Greater Bay Area - Lei, Weng Chi; Wang, Xinru (Economics and Finance Readings, 2023)
The degree of economic integration in the Guangdong-Hong Kong-Macau Greater Bay Area (GBA), as reflected in the mobility of trade and capital flows, has been strengthened by free trade agreements, but obstacles including border effects, capital controls, differences of exchange rate systems and inadequate cross-regional coordination remain. Digital renminbi (e-CNY) has been tested in Shenzhen, a core GBA city since April 2020. If e-CNY is adopted in the GBA, the area will effectively become a single currency zone. Whether the GBA constitutes an “optimum currency area” (OCA) depends on its degree of economic integration. This paper computes real interest rate differential (RID), uncovered interest rate differential (UID) and deviation from purchasing power parity (PPD) of each regional pair based on data of interest rates, exchange rates and price indexes from 2016M2 to 2022M7. All UID, PPD and RID series have means within about 1 percent point from 0, indicating high degrees of financial integration, real integration and economic integration. With the exception of Guangdong-Macau RID, all series are stationary, implying mean-reverting behavior. Hence, the parities are expected to hold both in the short run and in the long run, which is a condition for an OCA in the GBA. Furthermore, the regression analysis finds that the test launch of e-CNY in Shenzhen (adjusted for the COVID-19 outbreak) has significant impacts on all RIDs, Guangdong-Macau PPD and Hong Kong-Macau PPD. With merely two and a half years of test launch, the introduction of e-CNY already had impacts on overall economic integration in the GBA.
Keywords: Economic development policy; Economic integration; Exchange rate regime; Financial integration; Greater Bay Area; Optimum currency area

Digital and Sustainable Trade Facilitation in Western Balkans Countries - Toshevska-Trpchevska, Katerina; Lei, Weng Chi (Florence); Stojkoski, Viktor (European Scientific Journal, ESJ, 2024)
After the Covid-19 Pandemic crisis in international economic relations it became evident that climate-smart aspects should be considered when re-establishing a new international trade order. International organizations have proclaimed that this momentum should be used to include climate-smart trade and investment provisions to enable sustainable development. It has been acknowledged that trade has an important role to play in the global response to climate change, providing economies with tools to draw on in their efforts to mitigate climate change and to adapt to its consequences. In this paper we focus the analysis on investigating the digital and sustainable component of trade facilitation measures applied in Western Balkans countries. To evaluate the importance of trade facilitation measures and their digital and sustainable components we apply standard gravity model with the data from UN Global Survey on digital and sustainable trade facilitation. The results show that trade facilitation measures are important for improving and increasing trade among the Western Balkans countries. Especially, measures connected to improving transparency procedures in trade and measures for alleviating trade formalities are most significant for increasing bilateral trade among Western Balkans countries. With a lower level of importance are the measures for improving cross-border paperless trade between these countries.
Keywords: Digital and sustainable trade facilitation; UN Global Survey on Digital and Sustainable Trade Facilitation; Western Balkans countries; gravity model

COVID-19: Short-Run Impacts of the Pandemic on the Integrated Resort Oligopoly of Macao - Lei, Weng Chi (2021)
Objective: As a world tourist destination, Macao is inevitably under the impact of the COVID-19 pandemic. However, the market of integrated resorts in Macao are shared by only a few casino concessionaries, together forming an oligopoly. While the firms attempted to adjust price, quantity and quality of their hotel services in response to the pandemic, they could not overlook the strategic interactions with other players in the market. Hence, this paper aims to investigate the possible impact of the pandemic on the oligopolistic strategies in the integrated resort market in Macao. Methodology: Application of a theoretical model of differentiated oligopoly to this six-firm case shows that price differences across firms depend on their quality differentiation. In order to analyze these price differences empirically, this paper collects data of hotel room rates of the integrated resorts from November, 2019 to mid-August, 2020, covering the periods before and after the outbreak of COVID-19. Originality: In the existing literature, there is a lack of studies of the oligopoly in the hospitality industry of Macao. Furthermore, the effect of COVID-19 is still ongoing, so this present paper is one of the first to perform such analysis. Results: The regression of each of the hotel price differentials on the COVID-19 dummy variable shows that COVID-19 has statistically significant impacts on almost all the price differentials. Intuitively, MGM and Wynn were in the high-price segment before and after the outbreak, while other firms switched positions in the low-price segment during the pandemic. One obvious downstream movement was by Conrad. According to the proposition derived from the theory, these imply that COVID-19 should have significant impact on the quality differentiation of the firms. Practical implications: The results are in line with the observations that the integrated resorts have rolled out staycation packages according to preferences of local residents. These quality adjustments observed in Macao’s hospitality industry currently only involved variable inputs rather than fixed inputs of production; therefore, the impact of COVID-19 should be seen as short-term effects. Keywords: Covid-19; Differentiated oligopoly; Hospitality industry; Hotel room rate; Oligopolistic market structure; Pricing strategy.

Attitudes, Acceptance, and Registration toward Organ Donation in Macao - Lou, Kin Heng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

A STUDY OF GREEN FINANCIAL TECHNOLOGY ACCEPTANCE IN TONGZHOU DISTRICT OF BEIJING - An, Bo Yang (University of Saint Joseph, 2023)
China’s economy has entered a critical period of structural adjustment. The developing green industries and the transforming traditional industries have increasing demand for finance, making ""green finance"" increasingly essential. While China's green finance is in the development stage, some newly developed zones serve as pilots for the launch of green financial products. An example is Tongzhou District of Beijing, which aims to expand Beijing’s space, promote the coordinated development of Beijing-Tianjin-Hebei, and explore the optimal development mode of the densely populated economic areas. This thesis aims to study consumer acceptance of green financial technology (fintech) in the case of Tongzhou District. This thesis extended the commonly applied theoretical model for the problem of study, the Energy Augmented Technology Acceptance Model (EA-TAM), to analyze the impacts of perceived usefulness, perceived ease of use, attitude toward use, intention, usage intention, environmental awareness, and green knowledge on the acceptance of green fintech in Tongzhou District. The survey collected 403 valid responses from people that had been active in Tongzhou District. The quantitative analysis is based on structural equation modeling techniques, including reliability analysis, validity analysis, standard method deviation test, and hypothesis testing. The analytical results show that all the hypothesized factors are significant. In addition, the sample is divided into different gender groups and education groups, so that the impacts of the socio-demographic characteristics can be explored. Males’ environmental awareness and green knowledge are insignificant in determining their acceptance of green fintech. The low-educated group’s acceptance of green fintech does not significantly depend on environmental awareness and perceived usefulness
Keywords: Fintech; Green Gintech; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph